Biological investigations : Form, function, diversity & process - Dolphin, Warren D (Boston McGraw Hill Higher Education, 2005)
Contents: science: a way of gathering knowledge; techniques in microscopy; cellular structure reflects function; determining how materials enter cells; using quantitative techniques and statistics; modeling biological molecules,...
Includes bibliographical references.
Keywords: Dược học